The ontogenic study of early life stages of culture-bred Nomorhamphus sp. (Zenarchopteridae) from Lindu, Central Sulawesi - Muh Herjayanto; Odang Carman; Dinar Tri Soelistyowati; Alimuddin; Aryo Wenang Wicaksono; Harton Arfah (Jurnal Akuakultur Indonesia)
Nomorhamphus sp. is a freshwater fish that has been traded as an ornamental fish. This fish is unique as an endemic species with a halfbeak-like jaw and orange color on the caudal fin. However, this fish culture information needs a further information. Based on this condition, it is necessary to conduct a study as a basis for ornamental fish breeding and growing-out activities through domestication. A crucial problem in this fish is larval rearing, which can be observed through ontogeny studies. The study was conducted on the newly-born larval behavior, morphological development, andropodium development, growth, and survival rate at the early stages, namely larvae to juvenile. The results showed that the newly-born larvae of Nomorhamphus sp. Lindu had a total length of 1.6-1.8 cm. Larvae could swim four hours 22 minutes after birth and feed artemia nauplii with surface feeding type. The initial juvenile stage occurred 25 days of post-birth period with a total length of 2.0-2.2 cm. The water condition of the rearing during the study could support the larval transformation to juvenile. This study is the first report related to the aquaculture success of the early life stage of Nomorhamphus sp. Lindu at the domestication stage.